Role of Bruxism in Prosthetic Treatments- A Survey - Shabbarish Chockalingam1 , Keerthi Sasanka2 , Yuvaraj Babu K3 , Visalakshi Ramanathan4 , Dhanraj Gan (Indian Journal of Forensic Medicine & Toxicology, 2020)
Bruxism is a parafunctional habit of grinding of teeth and it results in an overload of occlusal loading thatputs on more pressure on the teeth and the subsequent prosthetics causing them to fail, it is a commonphenomenon affecting nearly 30% of the general population but is not looked into with deep detail. A surveyof 16 questions was sent to 114 respondents. The questionnaire was made on Google Forms, it had severaloptions for each question to get a response as accurate as possible. The incomplete responses were rejectedand the data was collected and compiled using SPSS software. The compiled data was compared with theresults of other studies and the important questions were discussed. This study conclusively found that theawareness of Bruxism and its effect on prosthetic treatments is high and that the data can be used in futuretreatments resulting in reduced failure of prosthetics due to habits such as